Population pharmacokinetic modeling of dexmedetomidine nasal spray in Chinese adults - Huang, Yuanyuan; Xu, Sheng; Djebli, Nassim; Jiang, Hao; Yang, Guoping (Frontiers in Pharmacology, 2025)
ObjectiveThe main objective was to build and qualify a population pharmacokinetic (PopPK) model for dexmedetomidine nasal spray in Chinese adults and explore the covariates affecting the PopPK model parameters.MethodsA population pharmacokinetic model was developed based on the results of 1,225 blood concentration points from 196 healthy volunteers (HV) and patients in phase I and phase III studies. Covariates significantly affecting pharmacokinetic characteristics were analyzed. Model selection was performed using nonlinear mixed-effects modeling (NONMEM), and covariates’ screening was conducted using the traditional stepwise forward inclusion and backward elimination methods. Bootstrap and pcVPC methods were used for model validation. Logistic regression modeling was used to analyze the relationship between the Cmax within 45 min and the proportion of subjects who achieved Ramsay Sedation Scale (RSS)≥3 within 45 min of intranasal administration.ResultsThe final model was a two-compartment model with first-order absorption and linear elimination. Inter-individual variability terms were estimated on clearance and absorption rate constant. The residual variability was described using combined proportional and additive error models. In the final model, body weight was included via theory-based allometric scaling (i.e., exponents of 0.75 for clearances and 1.0 for volumes of distribution). The absorption rate in the patients from phase III study was approximately 49% of that in the HV from phase I study. The estimated population typical values for CL, V2, Q, Vp, KA, F1, and ALAG in the final model were 35.3 L/h, 21.5 L, 116 L/h, 86.5 L, 0.523 h-1, 0.653, and 0.0592 h, respectively. Bootstrap results confirmed the stability and reliability of the model, while pcVPC demonstrated good model fit. Logistic regression modeling revealed a significant exposure-response relationship between Cmax within 45 min and the proportion of RSS ≥3. The concentration slope was 0.01, while the intercept was 0.27.ConclusionThe present analysis successfully established a PopPK model for dexmedetomidine nasal spray in Chinese adults, confirming that body weight influences distribution and clearance. This PopPK model is being further explored to support pediatric dose recommendation.